An Intervention: Gadget-Free to Improve Sleep Quality - Elrisfa Magistarina; Zakwan Adri; Verlanda Yuca; Mutiara Fitriani (Jurnal Neo Konseling, 2021)
Sleep is a necessity of human life. Sleep helps humans to maintain their fitness and physical health. One of the psychological disorders that are difficult to overcome is difficulty sleeping. Sleep difficulties also occur in students who need adequate rest time to study well. Several studies have shown that students experience sleep disturbances and the initial interview conducted by researchers stated that the same case occurred in students of the Psychology Department. This study aims to conduct a Gadget Free (GF) psychological intervention to improve sleep quality in students who have difficulty sleeping. The result shows that there was a significant differences in sleep quality between control group and experimental group. In addition, according to NGain Score, the intervention was effective to improve the sleep quality of respondent who was in the experimental group. Furthermore, this intervention can be used to improve the sleep quality in more widen community.